The Role of Anxiety and Cortisol in Outcomes of Patients With Covid-19 - Ramezani, Mahtab; Simani, Leila; Karimialavijeh, Ehsan; Rezaei, Omidvar; Hajiesmaeili, Mohammadreza; Pakdaman, Hossein (Basic and clinical neuroscience, 2020)
The outbreak due to Coronavirus Disease 2019 (COVID-19) is n global public health emergency and challenges psychological resilience. The central nervous system, endocrine system, and immune system are complex interacting systems. Cortisol has been implicated as the cause of a wide range of mental and physical health disorders; however, the impact of cortisol on outcomes in patients with COVID-19 is not clear. The current study enrolled patients with COVID-19 (onset of disease within 7 days of the first symptom) to evaluate the serum concentration of cortisol and levels of anxiety and depression using the Hospital Anxiety and Depression Scale (HADS) to investigate a possible relationship between cortisol, depression, and anxiety levels and outcomes of patients with COVID-19. A total of 30 patients with COVID-19 were studied. The levels of cortisol and HADS score in patients who died of Covid-19 were significantly higher in comparison with surviving patients (P<0.017 and P<0.001 respectively). We also found that the HADS score was positively correlated with serum cortisol levels (r= 0.842, P=0.004). Our findings showed that stress and anxiety are associated with patients' outcomes. Psychological interventions can improve the mental health of vulnerable groups during the COVID-19 epidemic.